Strategi Guru PAI Dalam Pembinaan Karakter Di SMPN 1 Mengkendek Kabupaten Tana Toraja - Asmiyati, Asmiyati; Akil, Muhammad; Nengsih, Ratika; Bunyamin, Andi; Mustamin, Mustamin (Al-Qalam: Jurnal Kajian Islam dan Pendidikan, 2025)
This qualitative research examines the strategies of Islamic Religious Education (PAI) teachers in fostering the character of students in class VIII A SMP Negeri 1 Mengkendek Tana Toraja, as well as the supporting and inhibiting factors. The study involved 7 students, PAI teachers, and the principal. Data were collected through observation, interview, and documentation. The results show that the teacher's strategy, which includes discipline, habituation, and exemplary, is effective in character building. Family and extracurricular support play an important role, but lack of family attention and students' bad habits become obstacles. School, family and community collaboration is crucial to create a conducive environment for more optimal character development.